All-in-One E-Book Development in Proposing Automatic Critical Thinking Skill Assessments - Alif Syaiful Adam; Edi Supriana; Nasikhudin (Studies in Learning and Teaching, 2023)
Many e-books have been developed to learn specific physics concepts with comprehensive features. This means that e-books not only contain the primary components such as animations, videos, and illustrations but also many of them are equipped with virtual experiments. However, these e-books often need more integration of the assessment process, which is an important part of the learning experience. To address this, an all-in-one e-book concept called Aneboo has been developed. Aneboo includes interactive physics illustrations, virtual laboratories, worksheets, videos, and critical thinking assessments, all built into a single media platform for learning the concept of static fluids in junior high school. Additionally, Aneboo examines its function in automatically assessing critical thinking skills. The development of Aneboo follows the Hannafin & Peck development model, which includes needs assessment, design and development, implementation, and identification of similarities between manual and automatic scoring. As a result, Aneboo has achieved a validation score ranging from 95% to 97%. Moreover, Aneboo has the potential to automatically assess critical thinking skills through the similarity check feature embedded in the media.